Overimitation in Kalahari Bushman Children and the Origins of Human Cultural Cognition - Nielsen, Mark; Tomaselli, Keyan (Psychological Science, 2010)
Children are surrounded by objects that they must learn to use. One of the most efficient ways children do this is by imitation. Recent work has shown that, in contrast to nonhuman primates, human children focus more on reproducing the specific actions used than on achieving actual outcomes when learning by imitating. From 18 months of age, children will routinely copy even arbitrary and unnecessary actions. This puzzling behavior is called overimitation. By documenting similarities exhibited by children from a large, industrialized city and children from remote Bushman communities in southern Africa, we provide here the first indication that overimitation may be a universal human trait. We also show that overimitation is unaffected by the age of the child, differences in the testing environment, or familiarity with the demonstrating adult. Furthermore, we argue that, although seemingly maladaptive, overimitation reflects an evolutionary adaptation that is fundamental to the development and transmission of human culture.